2022
DOI: 10.1039/d2ta06128g
|View full text |Cite
|
Sign up to set email alerts
|

High entropy stabilizing lattice oxygen participation of Ru- based oxides in acidic water oxidation

Abstract: A novel Ru-based high entropy oxide electrocatalyst RuNiMoCrFeOx/CNT was successfully synthesized, where the OER tends to proceed through the LOM on the high entropy surface, high entropy stabilizes the lattice oxygen to participate in the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 57 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…It has been demonstrated that the electric double-layer capacitance ( C dl ) obtained from CV is proportional to ECSA; therefore the C dl was compared. 42 As shown in Fig. 3C, the C dl value (57 mF cm −2 ) of Co–Co 6 Mo 6 C 2 @NPC is ten times that of Co@NC (5.7 mF cm −2 ), indicating that Co–Co 6 Mo 6 C 2 @NPC has more active sites and larger ECSA.…”
mentioning
confidence: 73%
“…It has been demonstrated that the electric double-layer capacitance ( C dl ) obtained from CV is proportional to ECSA; therefore the C dl was compared. 42 As shown in Fig. 3C, the C dl value (57 mF cm −2 ) of Co–Co 6 Mo 6 C 2 @NPC is ten times that of Co@NC (5.7 mF cm −2 ), indicating that Co–Co 6 Mo 6 C 2 @NPC has more active sites and larger ECSA.…”
mentioning
confidence: 73%
“…In addition, for FeMnCoCrNi HEA catalysts [214], it was also reported that no Cr signal was detected by energy-dispersive spectroscopy or XPS after the OER stability test in 0.1 M KOH at 100 mA cm −2 for 60 h, indicating a remarkable compositional change upon OER. Besides, other transition metals such as Ni, Fe, Mo, Mn and Zn were also reported to dissolve to some extent from the HEM catalysts during OER [198,217,228]. Apart from dissolution, nonoxide HEMs (e.g.…”
Section: Post-oer Characterisation Of Hem Catalystsmentioning
confidence: 99%
“…The chronopotentiometry operation witnessed that it remained below even 225 mV after 1500 h. With the features of high entropy oxide (HEO), Wang and co-workers reported RuNiMoCrFeO x nanoparticles on carbon nanotubes (CNTs) along with better OER performance compared to RuO 2 in 0.5 M H 2 SO 4 . 182 For RuNiMoCrFeO x /CNTs, excessive active sites and higher charge transfer rate offered outstanding OER activity compared to other controlled samples. In situ differential electrochemical mass spectrometry (DEMS) measurements with the isotope 18 O indicated that the OER proceeded through the LOM pathway, and the high conformational entropy stabilized the involvement of lattice oxygen in acid, making the RuNiMoCrFeO x /CNTs stable at a high current density of 100 mA cm −2 for 100 h. At last, two novel electrocatalysts including RuB 2 and RuTe 2 were developed for acidic OER.…”
mentioning
confidence: 94%